Determinant factors affecting the value of manufacturing companies in indonesia - Rahim, Rida; Alfajri, Doni; Nasfi, Nasfi (Faculty of Economics and Business Mulawarman University, 2021)
This study aims to examine the effect of investment decisions, funding decisions, and dividend policies on firm value of Indonesian manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The research sample consisted of 23 companies with 115 observations conducted during the period. Manufacturers, which process raw materials into semi-finished or finished goods, are identical with factories that use machinery, equipment, engineering techniques, and labour (Heizer & Render, 2015). The study found that partially the effect of investments with the proxy investment opportunity set (IOS) on firm value was positive and significant. It demonstrates the ability of a company to obtain and manage capital that ultimately has a positive impact on firm value. This study found that the effect of funding decisions on firm value was negative and significant. While the effect of dividend policy on firm value was proved to be positive but not significant. The study selected firm size as the control variable that had a positive but insignificant effect on firm value.